Diastereoselective Radical Hydroacylation of Alkylidenemalonates with Aliphatic Aldehydes Initiated by Photolysis of Hypervalent Iodine(III) Reagents. Issue 19 (24th March 2016) - Selvakumar, Sermadurai; Sakamoto, Ryu; Maruoka, Keiji
Abstract: Diastereoselective radical hydroacylation of chiral alkylidenemalonates with aliphatic aldehydes is realized by the combination of a hypervalent iodine(III) reagent and UV‐light irradiation. The reaction is initiated by the photolysis of hypervalent iodine(III) reagents under mild, metal‐free conditions, and is the first example of diastereoselective addition of acyl radicals to olefins to afford chiral ketones in a highly stereoselective fashion. The obtained optically active ketones are useful chiral synthons, as exemplified by the short formal synthesis of (−)‐methyleneolactocin. Abstract : Iodine(III) + light : The first diastereoselective radical hydroacylation between aldehydes and olefins initiated by the photolysis of hypervalent iodine(III) reagents is described. Various chiral ketones were obtained in a highly stereoselective fashion. The utility of this methodology was demonstrated by the formal total synthesis of (−)‐methyleneolactocin.